If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -36x + 2 = x Reorder the terms: 2 + 12x + -36x = x Combine like terms: 12x + -36x = -24x 2 + -24x = x Solving 2 + -24x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + -24x + -1x = x + -1x Combine like terms: -24x + -1x = -25x 2 + -25x = x + -1x Combine like terms: x + -1x = 0 2 + -25x = 0 Add '-2' to each side of the equation. 2 + -2 + -25x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -25x = 0 + -2 -25x = 0 + -2 Combine like terms: 0 + -2 = -2 -25x = -2 Divide each side by '-25'. x = 0.08 Simplifying x = 0.08
| 16t^2+85t-50=0 | | 54=2(x-2)+2(x-(x-5)) | | 4x-4=5x+1 | | 15n-7n+6=46 | | 5y-6y+3y= | | 2x-(3x-3)=2 | | 5(x-7)-6=-41 | | 3t-2=19 | | 8x+8=3-2x-5 | | x^2+13x-42=0 | | -4y-8=6y+12 | | 3x=16-10 | | -(-6x+2)=-3(1-2x)-8x | | 2=2q-(5q+3) | | y^2+y+56=0 | | 4p-p-p-p-p-p-p+2p= | | x+60=4x | | 13v-8v-13=0 | | 10=-5(3+3r)-6r | | 7(3x+1)=28 | | 9+4x=-2x+21 | | 5x+97=11x-5 | | 123-6x=21x+18 | | y^2-10y+12=0 | | 6r+11=89 | | -.11x-6=-1 | | 7t+53=14+6t | | x^2-4x+140=0 | | 2x-5=2x-6 | | 9-12x-x^2=0 | | (2x+5)(6x+4)= | | 3x-x=10x-66 |